Decreasing Corn Particle Size Increases Metabolizable Energy When Fed to Gestating Sows - Gage E. Nichols; Caitlin E. Evans; Julia P. Holen; Rachel N. Kort; Haley K. Wecker; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Previous research has demonstrated that reducing the particle size of corn improved metabolizable energy (ME) utilization in many phases of swine production. One phase that has had limited research thus far is the gestating phase for sows. The objectives of this paper were to determine the effects of corn particle size on the digestibility of gross energy (GE), and determine the digestible energy (DE) and ME in gestating sow diets. A total of 27 sows during the second phase of gestation (d 40 to 74) were chosen and fed a common diet with corn ground to 1 of 3 target average particle sizes (geometric mean diameter; dgw) of 400, 800, or 1200 μm. Corn was ground using a 3 high roller mill (RMS model 924). Titanium dioxide (0.25%) was included in the diet as an indigestible marker for index digestibility calculations. Sows were fed experimental diets for 7 d to allow for diet adaptation before a 2-d collection period. At the beginning of the collection period, sows were fitted with a urinary catheter and urine was collected in buckets containing 20 mL of sulfuric acid. Fecal grab samples were also collected from each sow during the collection period. Subsamples were taken, mixed, analyzed for GE, and titanium levels to determine digestibility of gross energy and to calculate DE and ME. The ME of corn was calculated by subtracting the ME of soybean meal (1,494 kcal/lb) and soybean oil (3,889 kcal/lb) from diet ME, utilizing the NRC 2012 values for those ingredients. Apparent total tract digestibility (ATTD) of GE and calculated DE, ME, and corn ME content increased (linear,P<0.001) as corn particle size was reduced from 1200 to 400 μm. The ME of the diet (88.5% DM) increased by 81 kcal/lb as the dgwwas reduced from 1,200 to 400 μm. The calculated corn ME (88.5% DM) also increased by 103 kcal/lb as the dgwwas reduced from 1,200 to 400 μm. Utilizing a linear regression model and the analyzed corn particle size data herein, it was determined that for every 100 μm reduction in corn dgwfrom 1,372 to 404 μm, the ME value of corn is increased by 10.7 kcal/lb.
Keywords: particle size; metabolizable energy; gestating sows